Tổng hợp Co3O4 kích thước nanomet bằng phương pháp đốt cháy gel - Đại, Lưu Minh; Loan, Nguyễn Thị Tố (Vietnam Journal of Chemistry, 2012)
Co3O4 powder has been synthesised at low temperature (600oC) by the combustion of gel prepared from polyvinyl alcohol (PVA) and cobalt nitrates. Factors affecting on synthesis process of nanometer oxides Co3O4 including temperature and pH of gel formation, molar ratio of cobalt concentration and polyvinyl alcohol concentration, temperature of calcining on structure and parcticles sizes were investigated. The crystalline process and the morphology of oxides particles were considered by X-Ray diffraction (XRD), Scanning Electron Microscopy (SEM). Surface areas of oxides were determined by the BET (Brunaure-Emmet-Teller) method. Further thermal treatment at 400 – 700oC for 2 hours yields the single phase Co3O4 with a specific surface area 39.68 m2/g.